Morphological and anatomical patterns in Pontederiaceae (Commelinales) and their evolutionary implications - Lima de Sousa, Danilo Jose; Scatena, Vera Lucia [UNESP]; Giulietti, Ana Maria; Oriani, Aline [UNESP] (Elsevier B.V., 2016)
Pontederiaceae include six genera and approximately 35 species of aquatic plants. The family exhibits great variation in morphology that makes the characterization of species and the understanding of infrafamilial relationships difficult. Twenty species were studied from collections made at the reproductive stage, aiming to establish morphological and anatomical patterns to better understand the taxonomy and evolution of the family. In order to include all species of the family, herbarium specimens were analyzed together with information available in the literature. Four morphological patterns were established for the family: Pattern I-stems with short internodes and alternate, petiolate leaves; Pattern II stems with long internodes and alternate, petiolate leaves; Pattern III-stems with long internodes and alternate, sessile leaves; Pattern IV-stems with long internodes and verticillate, sessile leaves. The stems have atactosteles and in the species of Pattern I they are rhizomatous. The leaf petiole, the reproductive axis, the inflorescence bract petiole and the peduncle have monosteles and are distinguished from one another by the number of rings of collateral vascular bundles, and by the presence or absence of a fistula. The morphological patterns may represent synapomorphies of infrageneric groups and are related to the life form of the species. Based on current phylogenies, Pattern I is a plesiomorphic condition, including emergent species, and Patterns III and IV are the most derived and include submersed species. This is consistent with variation in water availability in the environment having influenced the diversification of Pontederiaceae during the course of their evolution. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aquatic plants; Brazilian semi-arid; Evolution of vegetative characters; Water availability